2005
DOI: 10.1242/jeb.01859
|View full text |Cite
|
Sign up to set email alerts
|

Cryoprotection by urea in a terrestrially hibernating frog

Abstract: SUMMARY The role of urea as a balancing osmolyte in osmotic adaptation is well known, but this `waste product' also has myriad other functions in diverse taxa. We report that urea plays an important, previously undocumented role in freezing tolerance of the wood frog (Rana sylvatica), a northern woodland species that hibernates terrestrially in sites where dehydration and freezing may occur. Wood frogs inhabiting an outdoor enclosure accumulated urea to 65 mmol l-1 in autumn and early winter, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
103
1
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(115 citation statements)
references
References 75 publications
(64 reference statements)
8
103
1
3
Order By: Relevance
“…In those month they would probably were making them metabolically competent for the coming harsh winter. Our present findings therefore strongly indicate link between elevated urea level and cryoprotection as indicated by Costanzo and Lee (2005). It may be concluded that in the common Indian toad decline in thyroid hormone concentration has its behavioral and physiological response that leads to sustain increased cholesterol level in serum, which seems to be the most important metabolite during the hibernating phase.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…In those month they would probably were making them metabolically competent for the coming harsh winter. Our present findings therefore strongly indicate link between elevated urea level and cryoprotection as indicated by Costanzo and Lee (2005). It may be concluded that in the common Indian toad decline in thyroid hormone concentration has its behavioral and physiological response that leads to sustain increased cholesterol level in serum, which seems to be the most important metabolite during the hibernating phase.…”
Section: Discussionsupporting
confidence: 73%
“…Acclimatization to low temperature causes changes on their system to maintain catalytic potential or to alter the relative activities of different metabolic pathways at low temperature (Hochachka and Somero, 1984). Available reports indicate that environmental cold stress in hibernating toads causes significant changes in plasmaprotein and glucose (Churchill and Storey, 1993;Edwards et al, 2004;Costanzo and Lee, 2005), blood urea ( Jorgenensen, 1997;Costanzo and Lee, 2005 ). Effect of cold stress can also produce remarkable changes in blood urea concentration (Jorgenensen, 1997, Costanzo andLee, 2005,) which probably help the animal to cope with low temperature and act as a cryoprotectent agent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among amphibians, this response is best exemplified by members of the gray treefrog complex (genus Hyla), which potentially can accumulate glycerol to concentrations of 50-80μmolml −1 blood during cold acclimation (Layne and Stapleton, 2009;Zimmerman et al, 2007). Rana sylvatica (and perhaps other species) can accrue urea to comparable levels during autumn and early winter, coincident with seasonal declines in ambient temperature and water potential (Costanzo and Lee, 2005). In the present study this species amassed urea even in the absence of osmotic stress, a potent driver of urea accumulation in amphibians (Jørgensen, 1997).…”
Section: Overwintering Preparationsmentioning
confidence: 99%
“…In wood frogs, dehydration alone provokes a hyperglycemia response, comparable to the build-up of cryoprotectants during freezing (Churchill and Storey, 1993;Churchill and Storey, 1994a). Similarly, the build-up of urea to protect against colligative water loss is thought to be important in both dehydration and freezing (Costanzo and Lee, 2005;Muir et al, 2007). Parallel molecular responses have also been observed between wood frog dehydration and freezing, including reduced metabolism, activated liver glycogen phosphorylase and elevated PKAc and liver second messenger cAMP levels (Pinder et al, 1992;Churchill and Storey, 1994a;Holden and Storey, 1997).…”
Section: Discussionmentioning
confidence: 99%